Retention of Ascorbic Acid and Solid Concentration via Centrifugal Freeze Concentration of Orange Juice - P. Orellana-Palma; G. Petzold; I. Andana; N. Torres; C. Cuevas (Journal of Food Quality)
Freeze concentration of liquid foods produces high-quality concentrates while retaining the heat-labile compounds found in fresh samples. Centrifugal freeze concentration is a cryoconcentration method assisted by an external force, centrifugation, to enhance the separation of concentrate from the ice. When applying centrifugal freeze concentration to orange juice, after the third cryoconcentration cycle, the ascorbic acid content in the concentrate showed retention close to 70% of the initial value. After the third cycle, the solutes in the concentrate increased 4 times the initial value of the fresh sample with 70% efficiency. The color evaluation showed that the final concentrated fraction was darker than the fresh juice. The centrifugal freeze concentration in orange juice was effective for obtaining a high-quality concentrate with a higher concentration of solids and ascorbic acid retention.